Back to the lake : a reader for writers - Cooley, Thomas, 1942- (W.W. Norton & Co., 2015)
A new take on the traditional rhetorical modes, showing how they are used in the kinds of writing college students are most often assigned―arguments, analyses, reports, narratives, and more.